An evaluation of a structured learning program as a component of the clinical practicum in undergraduate nurse education: A repeated measures analysis. (January 2016) - Watt, Elizabeth; Murphy, Maria; MacDonald, Lee; Pascoe, Elizabeth; Storen, Heather; Scanlon, Andrew
Summary: Background: There is evidence that nursing students experience stress and anxiety and a reduction in self-efficacy when undertaking clinical placements. Previous reports have identified that a structured three-day program within the Bachelor of Nursing (BN) clinical practicum reduces the students self-report of anxiety and increases self-efficacy. However, it is unreported whether these improved outcomes are sustained for the duration of the clinical placement. Objective: The aim of this study was to evaluate the duration of the effect of a three-day structured learning program within the clinical placement on final year Bachelor of Nursing student's report of anxiety and self-efficacy pre- and post-program participation in this intervention and following completion of the clinical practicum. Design: A repeated measures design. Setting: University-based Clinical School of Nursing, acute care clinical practicum. Participants: Final year Bachelor of Nursing students. Methods: The intervention comprised the three-day program on starting the clinical practicum. A questionnaire included the anxiety subscale of The Hospital Anxiety & Depression Scale (The HAD) and the General Self-Efficacy Scale (GSES-12). The questionnaire was completed on day one (time one), upon completion of the three-day program (time two) and upon completion of placement on day 18 (time three). Results: The questionnaire response rate varied over time. There was a statistically significant effect in reducing anxiety over time: F (1.73, 74.46) = 25.20, p  < 0.001 and increasing self-efficacy over time F (1.32, 41.04) = 7.72, p  < 0.004. Conclusions: This is the first report that we are aware of that has measured final year Bachelor of Nursing student's report of both anxiety and self-efficacy over repeated measures of time. Students continue to benefit from a structured learning program and the benefit of the intervention is sustained for the clinical placement duration. Highlights: We evaluated a structured clinical program for final year Bachelor of Nursing students. There was a statistically significant effect in reducing anxiety and increasing self-efficacy. The effect was sustained for the duration of the clinical placement.